IMPLEMENTASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI SEKOLAH RUJUKAN NASIONAL TK ‘AISYIYAH 4 TEBET JAKARTA SELATAN - Khusniyati Masykuroh (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2020)
Clean and Healthy Behavior (PHBS) is important to instill from an early age and must be supported by all parties. Clean and healthy living habits will support early childhood to grow and develop optimally. School has an important role in shaping these behaviors. This study aims to find out an overview of the implementation of PHBS, the methods used, and the impact of the implementation of PHBS in TK ‘Aisyiyah 4 Tebet, South Jakarta. The method used is a qualitative research by collecting data through observation, interviews, and documentation. The researcher as the main instrument in research used observation, interview, agnd documentation guidelines. Data analysis was carried out through three data reduction channels, data presentation and conclusion drawing. As for the validity of the data, triangulation of various sources is used. The results showed that: 1) The implementation of PHBS in TK ‘Aisyiyah 4 Tebet was carried out through health education, health services, and fostering a healthy environment; 2) The methods used in the implementation of PHBS are counseling, examination, movement and song, demonstration, direct practice, habituation, and exemplary; 3) The impact of implementing PHBS can be seen from the increased awareness of students to behave cleanly and healthy, such as throwing trash in their place, raising clean clothes, styling hair neatly, consuming healthy food, washing hands before eating, using lavatory to urinate and defecate, and brushing teeth diligently; and the school received an award as 1st Winner of Healthy School in DKI Jakarta in 2017, and 4th best National Healthy School in 2018, the national pilot of all Aisyiyah kindergarten, and the apprentice of headmasters and teachers of PAUD ‘Aisyiyah pilot area at the regional level.